Optimization of Product Oil Shipment System for Archipelegic Region - Pratiwi Wuryaningrum; Tri Achmadi; Achmad Mustakim; Hasan Iqbal Nur; Siti Dwi Lazuardi; Marita Kusumadewi (Universitas Trunojoyo Madura, 2019)
Demand of products oil continues to increase by increasing the mobilization in various areas in Indonesia. The government should rethink considering the uneven spread of demand and supply of products oil that can not be mixed in the cargo hold. Currently product oil deliveries to Nusa Tenggara Barat carried by tanker vessels. The issue is whether the vessel’s size not yet optimum. The purpose of this study is to optimize the distribution of product oil from Transit Terminal Product Oil to Unloading Ports. The most influenced variable are the size of the main vessel and the effect on the primary measure is the amount of goods transported. The main dimensions of tanker are LPP= 105 m; B= 18,01 m; H= 8.23 m T= 6.78 m ;DWT= 7,992 DWT ;Payload = 8,933 KL and Tankers’s unit cost is Rp. 203,587.70 per Kiloliter